Pengaruh Beban Kerja terhadap Komitmen Pekerjaan pada Guru di MTS Arrahmah - Evi Husniati Sya'idah; Tontowi Jauhari (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effect of workload on teacher job commitment at MTs Arrahmah. The research method used was a quantitative approach with a descriptive-explanatory design. The study population was all 35 teachers at MTs Arrahmah, with a total sampling technique. Data were collected through a closed-ended Likert-scale questionnaire and analyzed using simple linear regression with t-tests and F-tests at a significance level of 0.05. The results showed that workload had a significant and negative effect on teacher job commitment, as evidenced by the calculated F-value of 8605.199 with a significance level of 0.000 (p < 0.05), and a regression coefficient of -1.153. These findings indicate that any increase in workload will decrease teachers' job commitment. The conclusion of this study is that excessive workload, particularly in the context of madrasahs with academic and religious responsibilities, can reduce teachers' job commitment. Therefore, proportional workload management is necessary to maintain and enhance teacher commitment to the institution.   Keywords: Workload, Job Commitment, Madrasah Teachers, Mts, Educational Management